ART AND GRAPHIC DESIGN AND THEIR ROLE IN CURING OUT CONTEMPORARY ISSUES AND BEHAVIORS - Dr. Abdel Raheem Awad Abdel kareem (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Art and graphic design considered of the areas of visual arts that focuses on behavior through art to promote awareness of the aesthetic sense of individuals through shape, color, space, line and form. So, these arts offer its vision to serve precise purposes of interest to communities and to serve individuals, also a promoter for any issues through great self-impact formulation of aesthetically creations, coordination. Fine arts and graphics are one of the expression forms of social problems and present in the handling of negative thoughts, and improve unacceptable human behavior (1). because art is formerly narrowly linked to life. and if separated from life, life will be contracted and lost one of the most important factors of happiness and pleasure and progress. Since society is always in a state of change and development, inevitably there must be some new issues, difficulties, and social phenomena that are alien to society, and possibly provisional, which constitute a problem that urgently needs solutions. When we read the social situations and what the society is going through events and social difficulties and defects, we must address these undesirable behaviors. This research confirms the presence of plastic art and graphic design in all the issues of contemporary social matters and behaviors, and the care of these arts to indicate topics that concern social values and the improvement of ethics, behaviors and relations with a human message to address urgent issues.